An Empiric Experience Implementing a Methodology to Improve the Entrepreneurial Support System: Creating Social Value Through Collaboration and Co-creation - Cearra, Jokin; Saiz-Santos, María; Barrutia, Jon (Frontiers in Psychology, 2021)
Entrepreneurs are considered an important source of innovation, acting as agents of change in developed societies. For entrepreneurs to develop, entrepreneurial ecosystems are required. These environments are complex heterogeneous systems. However, the atomization of the subsystem of agencies and organisms supporting entrepreneurial activity can cause problems. To solve this governance problem, a social experiment was designed to test the value of a solution based on a technological platform. The methodology is based on a dynamic scheme, seeking the involvement and collaboration of all the stakeholders. This method uses a co-creative process inspired by design thinking. The theoretical framework included literature on entrepreneurial ecosystems and governance theory and took into account the need to involve all the stakeholders to improve the previous situation and achieve sustainable development goals. Based on the application and an ad-hoc methodology seeking the involvement and collaboration of all stakeholders, a social network supported by an ICT-based platform was formally created, contributing to alleviate the atomization problem and generating social value at the same time. This social experiment, carried out in the Spanish province of Biscay in the Basque Country, was a pilot test and could be extended to other entrepreneurial ecosystems with similar casuistic frameworks.